Exploring opportunities around climate-smart breeding for future food and nutrition security - Balié, Jean; Cramer, Laura K.; Friedmann, Michael; Gotor, Elisabetta; Jones, Christopher S.; Kozicka, Marta; Kruseman, Gideon K.; Notenbaert, An Maria Omer; Place, Frank; Rebolledo, María Camila; Thornton, Philip K.; Wiebe, Keith D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
There is a 95% chance that warming will exceed 2°C by the end of the century (Raftery et al. 2017). Global crop productivity is projected to fall by 5-10 % per degree of warming (Challinor et al. 2014), with even greater losses likely for some crops in some areas. The challenge of meeting future food demand is increasing, and climate change is already diminishing our ability to adapt through crop breeding (Challinor et al. 2016; Aggarwal et al. 2019). Recent research is suggesting that increases in climate variability are already affecting the number of food-insecure people, and that increasing atmospheric CO2 concentrations may affect the nutrient content of some food staples, with serious implications for food and nutrition security (Smith and Myers 2018).